Legitimacy Politics - Dellmuth, Lisa; Tallberg, Jonas (Cambridge University Press, 2024)
This book focuses on how contestation among elites shapes the legitimacy of international organizations in the eyes of citizens. It offers fresh insights into major issues of our day, such as the rise of populism, the power of communication, the backlash against global governance, and the relationship between citizens and elites.